Low attendance of patients with intermittent claudication in a German community-based walking exercise program - Müller-Bühl, Uwe; Engeser, Peter; Leutgeb, Rüdiger; Szecsenyi, Joachim (International angiology, 2012)
AIM: Exercise therapy is an efficacious treatment for patients with peripheral arterial disease (PAD). The study aimed to determine the initiation and adherence of PAD patients with intermittent claudication in a supervised community-based walking exercise program. METHODS: Over a period of one year, PAD patients with Fontaine stage II attending an angiological outpatient setting were consecutively recruited to the study. Willingness, commencement and adherence of patients in the training program were recorded. RESULTS: Of 462 patients with intermittent claudication, only 166 (36%) subjects fulfilled the requirements for participation in physical exercise training. Of these eligible patients, 110 (66%) persons accepted the invitation to attend exercise therapy. However, despite the commitment, 58 (35%) subjects failed to initiate attendance in the training program. Fifty-two (24%) patients did start the program but 16 (8%) patients did not complete more than three initial training sessions. Over a three-month period, regular attendance was registered for 36 (16%) patients. CONCLUSION: Although physical exercise improves symptoms and mobility of patients with intermittent claudication, only about one-third of them is commencing an exercise program. Through lacking initiation and discontinuation, only a small percentage of claudicants permanently engages in a walking exercise program.